Miskonsepsi Siswa Sekolah Dasar tentang Konsep IPA : Studi Kasus di kelas VI SDN 024755 - Amelia Fariza; Assha Uli Handayani Hasibuan; Eirene Carolina Simamora; M. Hafiz Ermawan; Nadya Shadrina Siregar; Nilam Mirzah; Sister Imelda Lumban Gaol (Jurnal Bintang Pendidikan Indonesia, 2025)
Elementary School Students’ Misconceptions about Science Concepts: Case Study in Grade VI of SDN 024755 This study aims to identify and analyze the misconceptions held by sixth-grade students at SDN 024755 regarding basic science concepts. The research method used is a case study with a qualitative approach. Data were collected through interviews, observations, and diagnostic tests specifically designed to reveal students’ misconceptions. The results show that most students struggle with understanding certain science concepts, such as the water cycle, photosynthesis, and gravity. The misconceptions found include incorrect understandings of the processes of evaporation and condensation, the role of chlorophyll in photosynthesis, and the concepts of force and motion. These findings highlight the need for more effective teaching approaches in introducing and reinforcing science concepts at the elementary school level. Recommendations from this study include developing more interactive and contextual learning strategies to address students’ misconceptions, as well as improving the quality of teacher training in science education.